Optimal Route Selection Strategy in Wireless Mesh Networks - Sarao, Pushpender; Raghavendra Gupta, T; Suresh, S (International Journal of Computer Sciences and Engineering, 2025)
A wireless communication network offers a flexible information transport platform that allows mobile users to roam without suffering intolerable performance degradation networking. Due to the complex infrastructure and mobility of nodes that led to dynamic network topology, therefore, the routing is one of the most important challenges in wireless mesh networks. To overcome these challenges, a number of routing techniques have been developed. This paper focuses on finding the optimal path which using to transfer data. Here, a fuzzy based model (using three input parameters and one output parameter optimal route) is proposed in order to mimic the route discovery mechanism in routing protocols with using new parameters like (Number of hops, Local Battery level, Received Signal Strength Indicator) as the input to fuzzy inference system. A number of fuzzy rules are generated which are very important in reasoning processes for making a final decision about what is path most select.